Mapping Identification of Potential Cultural Tourism Areas Study Case: Kampung Parikan, Surabaya City - sucipto sucipto; Siti Nuurlaily Rukmana (Universitas Islam Sultan Agung Semarang, 2019)
ABSTRACKMapping the tourism potential will facilitate the process of development and management. The community of Kampung Parikan has not been able to map the current tourism potential. It impacts on the direction and plans for the supervision of the village’s management and development. This study aims to identify the characteristics of the area and to map the potential of the Kampung Parikan, Surabaya. The research methodology uses descriptive qualitative and evaluative descriptive through scoring techniques (see the existence of the existing by adopting regulations Gubernur Yogyakarta No 36 Tahun 2014 About Culture Village / Village as an indicator of area / village / village / village culture). The results show that Kampung Parikan, Surabaya was appointed as the first Cultural Village by the Government of Surabaya City on March 1, 2018. Some of the potential attractions include Ludruk Community, Manunggaling Dwi Budoyo Art Performance, and Gadukan Bags. The results of calculations indicate that Kampung Parikan is in accordance with indicators of cultural villages with a score of 63,6%. So that Parikan Village in Surabaya City deserves to be a cultural tourism village.Keywords: Tourism Atrraction, Cultural tourism, Kampung Parikan ABSTRAKPemetaan potensi wisata akan memudahkan dalam proses pengembangan dan pengelolaan. Masyarakat kampung parikan masih belum mampu melakukan pemetaan potensi wisata yang ada. Hal tersebut, berdampak terhadap arah dan rencana manejemen pengelolaan dan pengembangan kampung tersebut. Tujuan dari penelitian ini adalah untuk mengidentifikasi karakteristik wilayah dan dilanjutin dengan pemetaan potensi kampung budaya Parikan Kota Surabaya. Metodologi penelitian ini menggunakan deskriptif kualitatif dan deskriptif evaluatif melalui teknik skoring (melihat keberadaan eksisting dengan mengadopsi Peraturan Gubernur Yogyakarta No 36 Tahun 2014 Tentang Desa/Kelurahan Budaya sebagai indikator kawasan/desa/kelurahan/kampung budaya). Hasil penelitian menunjukan bahwa Kampung Parikan Kota Surabaya telah ditetapkan sebagai Kampung Budaya pertama oleh Pemerintah Kota Surabaya pada Tanggal 1 Maret 2018. Beberapa potensi yang menjadi daya tarik wisata Komunitas Ludruk, Pagelaran Seni Manunggaling Dwi Budoyo dan Tas Gadukan. Berdasarkan hasil penghitungan bahwa Kampung Parikan sesuai dengan indikator kampung budaya dengan skor 63,6%. Sehingga Kampung Parikan Kota Surabaya layak menjadi kampung wisata budaya.Kata Kunci: Atraksi wisata, Wisata budaya, Kampung Parikan